2004
DOI: 10.1002/bit.20067
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying anisotropic solute transport in protein crystals using 3‐D laser scanning confocal microscopy visualization

Abstract: The diffusion of a solute, fluorescein into lysozyme protein crystals has been studied by confocal laser scanning microscopy (CLSM). Confocal laser scanning microscopy makes it possible to non-invasively obtain high-resolution three-dimensional (3-D) images of spatial distribution of fluorescein in lysozyme crystals at various time steps. Confocal laser scanning microscopy gives the fluorescence intensity profiles across horizontal planes at several depths of the crystal representing the concentration profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 51 publications
5
68
0
Order By: Relevance
“…Dynamic adsorption experiments performed with cross-linked tetragonal crystal in a stirred system showed no more change in the fluorescein solution's concentration after 1 -4 days, depending on the solution pH, whereas in unstirred system this took 3-8 days. During the experiments, there was no swelling of the crystals according to observations by Leica TCS SP confocal microscopy (Cvetkovic et al, 2004). These findings are in agreement with the literature (Morozova et al, 1996).…”
Section: Cross-linked Tetragonal Crystals: Influence Of Mops Concentrsupporting
confidence: 91%
See 2 more Smart Citations
“…Dynamic adsorption experiments performed with cross-linked tetragonal crystal in a stirred system showed no more change in the fluorescein solution's concentration after 1 -4 days, depending on the solution pH, whereas in unstirred system this took 3-8 days. During the experiments, there was no swelling of the crystals according to observations by Leica TCS SP confocal microscopy (Cvetkovic et al, 2004). These findings are in agreement with the literature (Morozova et al, 1996).…”
Section: Cross-linked Tetragonal Crystals: Influence Of Mops Concentrsupporting
confidence: 91%
“…Therefore, adsorption and diffusion are equally important in their influence of the net transport process. Diffusion of solutes in protein crystals has been the subject of several studies (Bishop and Richards, 1968;Botin and Morozov, 1985;Cvetkovic et al, 2004;Granick, 1942;Kachalova et al, 1995;O'Hara et al, 1995;Velev et al, 2000). Some of these studies suggested a high influence of adsorption on transport rates but did not investigate adsorption equilibria separately from diffusion rates (Botin and Morozov, 1985;Velev et al, 2000).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, the widely applied confocal laser scanning microscopy (CLSM) can only observe fluorescent species. Therefore, CLSM requires either fluorescent molecules (Tallarek et al, 2003, Cvetkovic et al, 2004, or small fluorescent marker molecules attached to macromolecules to allow for spatially resolved concentration measurements (Kasche et al, 2003). The quantification of concentration based on fluorescence intensity, however, has been demonstrated to be limited by the attenuation of light by the carrier matrix that results in depth-dependent calibration curves and prohibits the evaluation of (fast) dynamic diffusion problems (Heinemann et al, 2004).…”
Section: Figure 4-2mentioning
confidence: 99%
“…Moreover, immersion of the cross-linked crystals in aqueous solutions of organic dyes, drugs, and antibiotics results in uptake of the guest molecules specifically within the solvent channels of the protein lattice. [12][13][14][15][16] Here, we extend the above strategies for the sequestration of metal ions and their reduction products within the solvent channels of glutaraldehyde cross-linked lysozyme single crystals. We note that a related approach, but involving cross-linked virus crystals, has been used recently to template the deposition of Pt/Pd nanoparticles.…”
mentioning
confidence: 99%